Prespektif Historis Tentang Ilmu Falak - Imam Ghozali (HUMANISTIKA : Jurnal Keislaman, 2016)
The science of astronomy is the study of celestial objects, the sun, moon, stars and other planets. The development of astronomy had already started since the time before Islam, namely in Babylon, ancient Egypt, China, India, Persia, and Greece but merely observe some constellations sajabahkan often coupled with all sorts tahayyul that are fantasti. According to them all as the Lord's instructions that must be solved. Even in those days, people use more of the constellations to predict their daily lives, but in the subsequent period during the development of Islamic teachings, astronomy no longer like that, but it already has basicpada knowledge of the Koran and al-Hadith, and until now this technology are developing rapidly both in the theory or application.